Racial disparities in pediatric kidney transplantation in New Zealand. (14th July 2014) - Grace, Blair S.; Kara, Tonya; Kennedy, Sean E.; McDonald, Stephen P.
Abstract Racial disparities in transplantation rates and outcomes have not been investigated in detail for NZ, a country with unique demographics. We studied a retrospective cohort of 215 patients <18 yr who started renal replacement therapy in NZ 1990–2012, using the Australia and New Zealand Dialysis and Transplant Registry (ANZDATA). Primary outcomes were time to first kidney transplant, death‐censored graft survival, and retransplantation after loss of primary graft. Europeans and Asians were most likely to receive a transplant (92% and 91% transplanted within five yr, respectively), and Pacific and Māori patients were less likely to receive a transplant than Europeans (51% and 46%, respectively), reflecting disparities in live donor transplantation. Pacific patients were more likely to have glomerulonephritis and FSGS. Pacific patients had five‐yr death‐censored graft survival of 31%, lower than Māori (61%) and Europeans (88%). No Pacific patients who lost their grafts were re‐transplanted within 72 patient‐years of follow‐up, whereas 14% of Māori patients and 36% of European and Asian patients were retransplanted within five yr. Current programs to improve live and deceased donation within Māori and Pacific people and management of recurrent kidney disease are likely to reduce these disparities.